ECONOMIC AND EDUCATIONAL IMPACTS REGARDING THEREMOVAL OF ENGLISHLANGUAGE AS AN OFFICIAL LANGUAGEINPAKISTAN: - Dr. Noor Ahmed; Bijar khan; Kasi, Dr. Mirwais; Abdul Qadir (Al-Burz, 2017)
This paper examines the definite impacts of English language’s removal as an official language in Pakistan as well as analyzes critically whether the timing of the decision is a sane motive? English surely is the lingua franca and educational language in the world possessing the prime status regarding international communiqué. Scholastic development as accepted by globalization has to shifted the character of the English language. Whereas English has turned out to be an essential means increasing attractiveness in international arena, as the top developing countries are emphasizing more and more on English language to be universalized in all fields. Although the local languages do have their importance and may not be discarded to be used as official languages. The findings of this study reveal the possible economic impacts and common realism of different linguistic development as well as strategy creativities in the country as well as to recommend the better policies and planning for the actual use of local as well as English language.